Analysis of calcium signaling pathways in plants - Batistič, Oliver; Kudla, Jörg (Biochimica et biophysica acta, 2012)
Calcium serves as a versatile messenger in many adaptation and developmental processes in plants. Ca2+ signals are represented by stimulus-specific spatially and temporally defined Ca2+ signatures. These Ca2+ signatures are detected, decoded and transmitted to downstream responses by a complex toolkit of Ca2+ binding proteins that function as Ca2+ sensors. This review will reflect on advancements in monitoring Ca2+ dynamics in plants. Moreover, it will provide insights in the extensive and complex toolkit of plant Ca2+ sensor proteins that relay the information presented in the Ca2+ signatures into phosphorylation events, changes in protein–protein interaction or regulation of gene expression. Plants' response to signals is encoded by different Ca2+ signatures. The plant decoding Ca2+ toolkit encompasses different families of Ca2+ sensors like Calmodulins (CaM), Calmodulin-like proteins (CMLs), Ca2+-dependent protein kinases (CDPKs), Calcineurin B-like proteins (CBLs) and their interacting kinases (CIPKs). These Ca2+ sensors are encoded by complex gene families and form intricate signaling networks in plants that enable specific, robust and flexible information processing. This review provides new insights about the biochemical regulation, physiological functions and of newly identified target proteins of the major plant Ca2+ sensor families. This article is part of a Special Issue entitled Biochemical, biophysical and genetic approaches to intracellular calcium signaling. ► Plants contain a unique calcium signalling toolkit. ► Novel calcium reporter proteins advance our understanding of plant calcium signals. ► Plant calcium sensor proteins regulate diverse cellular functions.